Perlindungan Hukum Terhadap Saksi Pelapor (Whistleblower) Dalam Kasus Tindak Pidana Korupsi di Indonesia - Komang Ayu Trisna Dewi; Anak Agung Sagung Laksmi Dewi; Made Minggu Widiantara (Fakultas Hukum Universitas Warmadewa, 2025)
The title of this research is Legal Protection of Whistleblower Witnesses in Corruption Crimes Cases in Indonesia. The problems are (1) How is the legal regulation of whistleblower witnesses in corruption cases in Indonesia? (2) How is the legal protection of whistleblower witnesses in corruption cases in Indonesia? This research conducts a normative legal study using statutory and conceptual techniques. Primary, secondary, and tertiary online documents are the legal resources used. Descriptive-analytical techniques are used to evaluate legal materials. Legislation No. 31/2014 regulates the prerequisites for parties seeking LPSK protection, including provisions regarding research-based reporting. In Indonesia, individuals who disclose corruption cases as witnesses or